Direct and Indirect Effects Based on Changes-in-Changes - Martin Huber; Mark Schelker; Anthony Strittmatter (Center for Economic Studies and ifo Institute (CESifo), 2019)
We propose a novel approach for causal mediation analysis based on changes-in-changes assumptions restricting unobserved heterogeneity over time. This allows disentangling the causal effect of a binary treatment on a continuous outcome into an indirect effect operating through a binary intermediate variable (called mediator) and a direct effect running via other causal mechanisms. We identify average and quantile direct and indirect effects for various subgroups under the condition that the outcome is monotonic in the unobserved heterogeneity and that the distribution of the latter does not change over time conditional on the treatment and the mediator. We also provide a simulation study and an empirical application to the Jobs II programme.
Keywords: C21; 330; direct effects; indirect effects; mediation analysis; changes-in-changes; causal mechanisms; treatment effects